NEOGENE TECTONIC ROTATIONS IN THE VICINITY OF THE NORTH AEGEAN TROUGH: NEW PALAEOMAGNETIC EVIDENCE FROM ATHOS AND SAMOTHRAKI (GREECE) - Kondopoulou, D.; Zananiri, I.; Michard, A.; Feinberg, H.; Atzemoglou, A.; Pozzi, J.-P; Voidomatis, Ph. (Bulletin of the Geological Society of Greece, 2007)
The present study focuses on two post-orogenic plutons, the Athos (Grigoriou) and Samothraki granites, as well as the Samothraki volcanics, located in the vicinity of the North Aegean Trough. A detailed palaeomagnetic study was carried out, with the aim of constraining the age and mechanism of tectonic rotations. In addition, anisotropy of low field magnetic susceptibility (AMS) was studied and isothermal remanent magnetization (IRM) and thermomagnetic analyses were performed. Finally, a radiometric age for the Athos granite was obtained (43.3 ± 1.0 Ma K/Ar biotite). The measured declinations indicate clockwise rotations of the Athos (16.6°) and Samothraki (36.3°) blocks. The age of rotation is constrained to be <18 Ma at Samothraki, whereas the much smaller rotation of the Athos block can only be dated as younger than Eocene. Comparing the new palaeomagnetic data to the published dataset for Northern Greece, we suggest that the palaeomagnetically determined rotations in the vicinity of the North Aegean Trough are dominantly of post-Early Miocene age, and are controlled by major strike-slip faults and distributed "small" or minor faults.